Little Red Riding Hood - Hillert, Margaret; Connelly, Gwen (Chicago, Ill. : Norwood House Press, 2006)
A little girl meets a wolf in the forest on her way to visit her grandmother. Includes reading activities.
Keywords: Readers (Primary); Readers